Entrepreneurial Interest is Reviewed from Entrepreneurship Education, Family Environment, and Technopreneurship Literacy with Self-Efficacy as an Intervening variable - Ilma Wulansari Hasdiansa; Sitti Hasbiah (Pinisi Journal of Entrepreneurship Review, 2024)
Entrepreneurial interest is a person's feeling of interest in entrepreneurial activities and wanting to become an entrepreneur. Entrepreneurial interest is one of the predictors of entrepreneurial behavior. The purpose of this study was to examine whether there is an influence of entrepreneurship education, family environment, and technopreneurship literacy on entrepreneurial interest through self-efficacy as an intervening variable. This type of research uses quantitative research. The population in this study was 427 students of Entrepreneurship Makassar State University and the number of samples was 100 respondents Data collection techniques in this study used questionnaires. Meanwhile, the data analysis technique used is path analysis. The results of the research can be used as evaluation material for teaching staff or lecturers in order to guide students to entrepreneurial interests, so as to produce new businesses that are beneficial to the community.